Cloud-based Data Analytics for Employee Staffing: Integrated Full Circle Staffing Systems - Posthuma, Richard A.; Rad, Parand Mansouri (Advances in Social Sciences Research Journal, 2025)
This manuscript explains how cloud-based data analytics can be successfully integrated with online employee recruiting and selection procedures. Fundamentals of how the combination of different types of selection procedures with varying validity coefficients will result in predictable success rates for employees who are hired. These fundamental principles can be the core foundation that makes cloud-based recruiting and selection procedures more effective in organizations.